SOCIAL CRITIQUE IN HYBRID COMEDY-HORROR: A DISCOURSE ANALYSIS OF AGAK LAEN FILM - Ananda, Tiara Wirman; Wibowo, Arif Ardy (Journal of Pragmatics and Discourse Research, 2025)
This study examines the Indonesian comedy-horror film Agak Laen as a medium for social critique through the lens of discourse analysis. Employing Jones Abigails comedy theory, the research decodes narrative elements, satirical dialogues, and absurd situations to reveal critiques of social norms and collective behaviors. Using qualitative content analysis, and the study explores four thematic pillars: solidarity in chaos, irrational decisions yielding benefits, unconventional lives, and mistakes as learning opportunities. The film creatively uses humor to expose societal issues, such as moral compromise in group dynamics and the tendency to prioritize harmony over ethics. Through dark comedy, scenes like the accidental success of unethical shortcuts or group loyalty under pressure highlight the irony of everyday social interactions. Satirical dialogues, such as absurd debates on morality and justice, provoke critical reflection among audiences while maintaining entertainment value. The findings demonstrate how hybrid genres, particularly comedy-horror, provide an effective platform for conveying cultural messages and moral lessons in a palatable manner. The success of Agak Laen with over nine million viewers underscores the potential of such genres to merge entertainment with meaningful critique. This study contributes to the discourse on hybrid genres and their role in fostering social reflection within diverse cultural contexts. It offers insights for filmmakers seeking to blend narrative innovation with socio-cultural relevance.